2015
DOI: 10.1080/10282580.2015.1025633
|View full text |Cite
|
Sign up to set email alerts
|

You’ve got to fight to be white: the rural foundation of the new militia for race control

Abstract: In this paper, we situate the recent rise of racialized and often violent political discourse within a framework of a class-based conception of nature and property. In this theoretical work, we contribute to thinking about how Whites are racially constituted by showing how an understanding of whiteness among the far right is significantly linked to narratives surrounding rural spaces as havens of individualism and in sharp contrast to the perceived multiculturalism of the city. In developing our argument, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Colonial imagery and concomitant claims of (White) US exceptionalism were common at Tea Party rallies (Zeskind, 2012: 504) and inflect the discourse of the Trump-era Republican Party. Masculinist discourses of individualism, self-reliance and idealization of the rural 'frontier' are also present in the contemporary White militia movement's nativist constructions of a purposively White, armed community (Wood et al, 2015). Adopt A Sniper cultivates community with the far-right and militia movements, participating in gun shows (Wills, 2011), including the annual meeting of the National Rifle Association (Jackson, 2017), and counting Soldier of Fortune, a key publication of the new-right militia movement, as a supporter of the organization (AmericanSnipers.org, 2016).…”
Section: Settler Violence and The Racialized Romance Of The Militiamanmentioning
confidence: 99%
“…Colonial imagery and concomitant claims of (White) US exceptionalism were common at Tea Party rallies (Zeskind, 2012: 504) and inflect the discourse of the Trump-era Republican Party. Masculinist discourses of individualism, self-reliance and idealization of the rural 'frontier' are also present in the contemporary White militia movement's nativist constructions of a purposively White, armed community (Wood et al, 2015). Adopt A Sniper cultivates community with the far-right and militia movements, participating in gun shows (Wills, 2011), including the annual meeting of the National Rifle Association (Jackson, 2017), and counting Soldier of Fortune, a key publication of the new-right militia movement, as a supporter of the organization (AmericanSnipers.org, 2016).…”
Section: Settler Violence and The Racialized Romance Of The Militiamanmentioning
confidence: 99%
“…In response, an emerging body of research has begun to explore how social constructions of crime and related criminal justice responses account for what Eastman (2015) terms "white innocence," or processes that "rationalize, excuse, and overlook White deviance" (239). Some of this research explores how mug shots of White women are viewed with empathy (Dirks, Heldman, and Zack 2015), how White militant radicalization is often associated with aspirations for individualism rather than violence (Wood, Jakubek Jr, and Kelly 2015), and how mass shootings committed by young White men are often attributed to mental health factors rather than a predisposition to violence (Heitzeg 2015). Related research has also found that Whites are overrepresented as victims of crime as well as law enforcement officers in local television news (Dixon 2017).…”
Section: Protection Of White Bodiesmentioning
confidence: 99%